Synthesis, crystal structure, and X-ray diffraction data of lithium m-phenylenediamine sulfate Li2(C6H10N2)(SO4)2. Issue 2 (June 2021) - Zhou, Junyan; Chai, Congcong; Hao, Munan; Zhong, Xin
Abstract : A new organic–inorganic hybrid lithium m -phenylenediamine sulfate (LPS), Li2 (C6 H10 N2 )(SO4 )2, was synthesized under aqueous solution conditions. The X-ray powder diffraction study determined that the title compound crystallized in a monoclinic system at 300 K, with unit-cell parameters a = 7.8689(6) Å, b = 6.6353(5) Å, c = 11.8322(10) Å, β = 109.385(3) °, V = 582.77(8) Å 3 . Indexing of the diffraction patterns collected from 100 to 600 K reveals that LPS has no structural phase transition within the measured temperature range, and the volume expansion coefficient is approximately 2.79 × 10 −5 K −1 . The crystal structure was solved based on the single-crystal diffraction data with space group P 21 / m . Lithium and SO4 2− are found to form quasi-two-dimensional anti-fluorite [LiSO4 ] layers stacking along the c -axis, with m -phenylenediamine molecules inserted in the anti-fluorite layers and forming hydrogen bonds to the SO4 2− . This explains a moderate anisotropic expansion in LPS.